2014
DOI: 10.1039/c4ra07272c
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of ultrasound-assisted extraction of protein from egg white using response surface methodology (RSM) and its proteomic study by MALDI-TOF-MS

Abstract: The presented work proposes an approach based on proteomic techniques to identify proteins in egg white. Response surface methodology (RSM) with Box-Behnken design (BBD) was used to optimize the ultrasound-assisted extraction process of proteins from the egg white. The effects of extraction parameters, including trifluoroacetic acid (TFA) concentration, ultrasonic power and ultrasonic time on the extraction process of proteins were evaluated. The optimized extraction parameters were trifluoroacetic acid (TFA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…33,34 It was reported that water could be helpful to enhance swelling of plant material, while ethanol is believed to disrupt the bonding between the solutes and plant matrices. 35,36 The increase in the extractability of phenolic compounds with adding of water to ethanol can be attributed to the increase in permeability of plant tissues enabling better mass-transfer by diffusion. 37 However, high concentration of ethanol may increase the polarity of the solution, holding back the dissolution of phenolic compounds and then decreasing the extraction yield.…”
Section: Optimization Of Uae Conditionsmentioning
confidence: 99%
“…33,34 It was reported that water could be helpful to enhance swelling of plant material, while ethanol is believed to disrupt the bonding between the solutes and plant matrices. 35,36 The increase in the extractability of phenolic compounds with adding of water to ethanol can be attributed to the increase in permeability of plant tissues enabling better mass-transfer by diffusion. 37 However, high concentration of ethanol may increase the polarity of the solution, holding back the dissolution of phenolic compounds and then decreasing the extraction yield.…”
Section: Optimization Of Uae Conditionsmentioning
confidence: 99%
“…SNPs associating with early or late AW significantly were reported on chromosomes 1, 3, 5, 18, 19, 23 and Z by genome-wide association studies (Abasht et al, 2009). Albumen proteomic researches have greatly expanded the identified albumen proteins in various layer breeds (Guerin-Dubiard et al, 2006;Mann, 2007;D'Ambrosio et al, 2008;Mann and Mann, 2011;Wang et al, 2012;He et al, 2014). The changes of albumen protein components during the degeneration process was also reported (Omana et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…New field-specific procedures need to be developed to address these field-specific analytical challenges 15,17 . Research so far has focussed on the improvement of the solubilisation step [17][18][19][20][21][22] , and the combined use a protein deglycosidase enzyme to improve the detection of egg 23 .…”
Section: Introductionmentioning
confidence: 99%